2005
DOI: 10.1111/j.1939-1676.2005.tb02751.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine Digital Tumors: A Veterinary Cooperative Oncology Group Retrospective Study of 64 Dogs

Abstract: We compared clinical characteristics and outcomes for dogs with various digital tumors. Medical records and histology specimens of affected dogs from 9 veterinary institutions were reviewed. Risk factors examined included age, weight, sex, tumor site (hindlimb or forelimb), local tumor (T) stage, metastases, tumor type, and treatment modality. The Kaplan-Meier product limit method was used to determine the effect of postulated risk factors on local disease-free interval (LDFI), metastasis-free interval (MFI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 3 publications
10
65
1
Order By: Relevance
“…Affected digits in this study were primarily from the front limbs. A similar pattern is described in articles on neoplasia in the digits of dogs, 11,14 which speculate that possible reasons for this may be increased weight bearing on the front-versushind limbs and increased exposure to carcinogens during digging behavior. 11 No sex predilection for the development of neoplasia was present apart from adenocarcinoma, where females were overrepresented.…”
Section: Discussionsupporting
confidence: 72%
“…Affected digits in this study were primarily from the front limbs. A similar pattern is described in articles on neoplasia in the digits of dogs, 11,14 which speculate that possible reasons for this may be increased weight bearing on the front-versushind limbs and increased exposure to carcinogens during digging behavior. 11 No sex predilection for the development of neoplasia was present apart from adenocarcinoma, where females were overrepresented.…”
Section: Discussionsupporting
confidence: 72%
“…11 Melanoma is the second-most-common digital tumor in dogs, constituting 15.6% of these tumors, 6 and is less commonly associated with radiographic evidence of bone lysis. 11 Given the lack of osseous response in this case, osteosarcoma-which accounts for 6.3% of canine digital tumors 6 -was considered less likely.…”
Section: Discussionmentioning
confidence: 99%
“…11 Melanoma is the second-most-common digital tumor in dogs, constituting 15.6% of these tumors, 6 and is less commonly associated with radiographic evidence of bone lysis. 11 Given the lack of osseous response in this case, osteosarcoma-which accounts for 6.3% of canine digital tumors 6 -was considered less likely. Although digital metastasis from a primary bronchogenic carcinoma has been reported as one of the most frequently encountered digital tumors in cats, 16 a similar clinical syndrome has not been documented in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Mammary (Taylor et al, 1976;Gilbertson et al, 1983) and squamous cell carcinomas (O'Brien, 1992;Henry et al, 2005) have also been reported in the dog. Many of these cancers exhibit an increased prevalence in particular breeds of dogs (Table 2), indicating a genetic predisposition (Cadieu and Ostrander, 2007).…”
Section: Cancermentioning
confidence: 99%